2005
DOI: 10.1175/waf857.1
|View full text |Cite
|
Sign up to set email alerts
|

WSR-88D Radar, Tornado Warnings, and Tornado Casualties

Abstract: The impact of the installation of Weather Surveillance Radar-1988 Doppler (WSR-88D) radars in the 1990s on the quality of tornado warnings and occurrence of tornado casualties is examined. This analysis employs a dataset of tornadoes in the contiguous United States between 1986 and 1999. The date of WSR-88D radar installation in each National Weather Service Weather Forecast Office is used to divide the sample. Tornado warnings improved after the installation of Doppler radar; the percentage of tornadoes warne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 12 publications
1
85
0
Order By: Relevance
“…In comparison to the nocturnal tornado event percentage, 39.3% of tornado fatalities and 42.1% of killer tornadoes from 1950 to 2005 took place during the night. Results from a two-sample difference of proportion test [Rogerson (2001) Simmons and Sutter (2005a), which indicated that expected fatalities are significantly lower for daytime tornadoes than for those that occur at night.…”
Section: A Temporal Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison to the nocturnal tornado event percentage, 39.3% of tornado fatalities and 42.1% of killer tornadoes from 1950 to 2005 took place during the night. Results from a two-sample difference of proportion test [Rogerson (2001) Simmons and Sutter (2005a), which indicated that expected fatalities are significantly lower for daytime tornadoes than for those that occur at night.…”
Section: A Temporal Analysismentioning
confidence: 99%
“…Thus, tornadoes at night are almost twice as likely to kill as those during the daytime. Simmons and Sutter (2005a) used three time of day delineations, including "day," "evening," and "overnight", in their investigations of tornado vulnerabilities. In this study, we examine the vulnerability of similar time periods, but use the specific sunset-sunrise information in our calculations rather than arbitrary temporal designations.…”
Section: A Temporal Analysismentioning
confidence: 99%
See 3 more Smart Citations